SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN CALON SALES PROMOTION GIRL (SPG) PADA PT.MATAHARI DEPARTMENT STORE PASAR BESAR MALANG MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Fira Isfatul Faizah; Rahayu Widayanti; Mochamad Husni (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2024)
Matahari Department Store (MDS) is one of the leading retail company in Indonesia that provide equipment clothing, accessories, beauty products and home appliances at affordable prices. PT. MDS outlets spread over 131 stores located in 62 cities, supported by a team of 50,000 people and more than 1,200 local suppliers as well as more than 90% of purchase directly from sources in Indonesia. The number of employees led to the Human Resource Department (HRD) often have difficulty in selecting candidates for Sales Promotion Girl (SPG). Rekruetment policy employees are still influenced by the subjectivity of the decision makers. Subjectivity decision caused SPG received less qualified. SPG mistake in choosing a very big impact on the company because it affects the company's profitability and performance of services. The purpose of this research is the establishment of Decision Support System for the selection of candidates SPG using Simple Additive weighting method (SAW) on PT.Matahari Department Store Pasar Besar of Malang. The results showed that the candidate selection decision support system SPG using SAW method can help the HRD in the process of selecting candidates for SPG, so the power SPG received in accordance with the criteria of the company.